Detection of variability in apo(a) gene transcription regulatory sequences using the DGGE method - Zídková, Kateřina; Kebrdlová, Věra; Zlatohlávek, Lukáš; Češka, Richard (Clinica chimica acta, 2007)
Increased lipoprotein(a), Lp(a), concentration is an independent risk factor for premature atherosclerosis. Apolipoprotein(a), apo(a), determines properties of the lipoprotein and its production rate is the limiting step in Lp(a) particle formation. Subjects covering the whole range of Lp(a) concentration were separated into quintiles. A randomly chosen sample from each quintile was derived, there being a total number of 713 individuals. The DGGE method was used to scan the known transcription regulatory regions of apo(a) gene (promoter; DHII and DHIII enhancers) for variability and its distribution across quintiles. Besides 5 previously reported nucleotide substitutions (+121 G>A; +93 C>T; −1712 G>T; −1617 C>A; −1230 A>G) 16 unreported rare sequence variants were detected. All polymorphic variants were distributed throughout the quintiles with several significant differences. The novel +62 C variant was found only among individuals with Lp(a) levels over 16 mg/dl. The apo(a) gene transcription regulatory regions were not revealed to be extremely polymorphic. However, we should consider a combined effect of all polymorphic sites from the whole apo(a) gene locus, including the apo(a) gene length polymorphism, when dealing with high population variability of Lp(a) levels.